Analisis Nilai-Nilai Karakter dalam Permainan Tradisional Sebagai Media Pembelajaran IPS Berbasis Kearifan Lokal - Supriyanto Supriyanto; Isbandiyah Isbandiyah (JURNAL PERSPEKTIF PENDIDIKAN, 2026)
This study aims to analyze the character values embedded in traditional games and examine their relevance as a local wisdom-based Social Studies learning medium. The study employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, documentation, and literature review related to traditional games, character education, Social Studies learning, and local wisdom. Data analysis was conducted using an interactive model consisting of data collection, data reduction, data display, and conclusion drawing. The findings reveal that traditional games contain various character values that are essential for educational development, including cooperation, responsibility, discipline, honesty, tolerance, social care, hard work, and sportsmanship. These values are reflected in the rules of the games, patterns of interaction among players, and the process of achieving common goals during gameplay. In addition to serving as recreational activities, traditional games function as a medium for transmitting cultural heritage and local wisdom, thereby strengthening students’ cultural identity. In the context of Social Studies education, traditional games are highly relevant because they can be utilized as contextual, participatory, and meaningful learning media to develop students’ knowledge, social skills, and character. Therefore, the integration of traditional games into local wisdom-based Social Studies learning can serve as an effective strategy for strengthening character education while simultaneously preserving local culture in the era of globalization. Keywords: Traditional Games, Character Values, Social Studies Learning, Local Wisdom